The economics instructor's toolbox. (January 2019) - Picault, Julien
Abstract: Although seminal literature indicates that "chalk and talk" is still the predominant lecture method (Watts and Becker, 2008; Watts and Schaur, 2011; Ongeri, 2017), research more specific to millennials (Carrasco-Gallego, 2017; Leinberger, 2015; Litzenberg, 2010; Morreale and Staley, 2016) indicates multiple challenges for economics instructors who are teaching millennials; it suggests instructors need to adapt their teaching methods. They especially point out that millennials have a different skillset than previous student cohorts. Recently, multiple new teaching methods have been proposed in the economics literature. This paper reviews and discusses the most effective teaching methods specifically targeting millennials. New teaching methods clearly focus on the inclusion of popular culture and media, which are already a salient part of the day-to-day life of students. Improving students' engagement appears to be a paramount objective in the recent literature. Examples of methods reviewed in this papers are flipped classroom, student-crafted economics experiments, and the use of social media as a medium of instruction.